ChemInform Abstract: Chiral Resolution Through Stereoselective Transglycosylation by Sucrose Phosphorylase: Application to the Synthesis of a New Biomimetic Compatible Solute, (R)‐2‐O‐α‐D‐Glucopyranosyl Glyceric Acid Amide. Issue 18 (17th April 2014) - Wildberger, Patricia; Brecker, Lothar; Nidetzky, Bernd
Abstract: The sucrose phosphorylase catalyzed glycosylation of racemic glyceric acid amide (II) with sucrose (I) affords the new biomimetic glycoside (III) in high yield with complete regio‐ and diastereoselectivity.